Primary Tuberculosis of Tonsils : A Rare Case Report - Shravanthi Mantra Prithviraj; Shanthi Priya D; Deepak Raj K (Dr. Annil Mahajan, 2024)
The occurrence of tuberculosis primarily affecting the tonsils, without concurrent active pulmonary tuberculosis, is an exceptionally uncommon clinical condition. A 16-year-old otherwise healthy individual presented with a persistent sore throat, dysphagia, and cervical lymphadenopathy. Initial investigations, including throat cultures and serological tests, were inconclusive. However, a detailed clinical examination and imaging revealed an uneven tonsillar enlargement. Histopathological analysis of tonsillar tissue confirmed the diagnosis of primary tuberculosis. In our case, the absence of pulmonary involvement and the atypical presentation delayed the diagnosis. Timely recognition and appropriate management are crucial for preventing complications and transmission of the infection.